PENGEMBANGAN E-LKPD BERBASIS ANDROID UNTUK MENINGKATKAN KEMAMPUAN MENERAPKAN KONSEP BIOTEKNOLOGI DAN PERANNYA DALAM KEHIDUPAN MANUSIA BAGI PESERTA DIDIK SMP KELAS IX - Rani Wijayati; Muhfahroyin; Ratini (EDUBIOLOCK, 2025)
Abstract Producing E-LKPD Biology Class IX KD 3.7 by using the idea of biotechnology and its function in human life is the aim of the development research. Research & Development (R&D) or development research is the type of research that is employed. The 10-stage Sugiyono model which includes (1) potential and issues, (2) data gathering, (3) product design, (4) design validation, (5) design revision, (6) product trials, (7) product revision, (8) usage trials, (9) product revision, and (10) mass production is the model that is employed. Up until the seventh step, which is product revision, this research was conducted. Validators in the domains of language, design, and material conduct product validation. The product will then be tested on SMP Negeri 10 Metro class IX students during the 2023–2024 academic year when it has been deemed practical. A questionnaire was utilized as a data gathering tool to learn about the responses from the students. The validation analysis's findings fall into the "Appropriate" category based on an average of the material, design, and language domains. According to product testing findings, the "Decent" category had an average student response value of 3.